2014
DOI: 10.5935/abc.20140043
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience of Two National Centers in Transcatheter Aortic Prosthesis Implantation

Abstract: BackgroundTranscatheter aortic valve implantation is an effective alternative to surgical treatment of severe aortic stenosis in patients who are inoperable or at high surgical risk.ObjectivesTo report the immediate and follow-up clinical and echocardiographic results of the initial experience of transcatheter aortic valve implantation.MethodsFrom 2009 June to 2013 February, 112 patients underwent transcatheter aortic valve implantation.ResultsMean age was 82.5 ± 6.5 years, and the logistic EuroSCORE was 23.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A total of 1110 citations were identified, and 85 full‐length studies remained after carefully screening the title and abstract. A total of 28 studies, incorporating 51,530 patients, met our inclusion and exclusion criteria after reading the full text. Although there were two studies that had overlapping data, they reported on different clinical aspects that we wanted to address.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1110 citations were identified, and 85 full‐length studies remained after carefully screening the title and abstract. A total of 28 studies, incorporating 51,530 patients, met our inclusion and exclusion criteria after reading the full text. Although there were two studies that had overlapping data, they reported on different clinical aspects that we wanted to address.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of COPD ranged from 12.5% to 43.4% in patients who underwent TAVI . Several large registries reported that the burden of COPD varied from 22.8% to 28.0% , but the PARTNER trial reported the prevalence of COPD was 43.4% .…”
Section: Resultsmentioning
confidence: 99%
“…After adjustment for multivariate analysis, no clinical factors were correlated with outcomes, except for dyslipidemia, which may suggest that this comorbidity is related both to AS acceleration and its severity, as reported by others 39‐41 . Thus, in our population, factors that have been classically correlated with mortality such as chronic kidney disease and COPD did not maintain significance after adjustments 3,4,30,42,43 . Sinning et al 7 reported that a severe increase in sPAP measured preoperatively was associated with an increased risk of death (hazard ratio [HR], 3.3, p = .003) and a higher incidence of comorbidities such as peripheral vascular arteriopathy, CAD, chronic kidney disease, and atrial fibrillation.…”
Section: Discussionmentioning
confidence: 50%
“…[39][40][41] Thus, in our population, factors that have been classically correlated with mortality such as chronic kidney disease and COPD did not maintain significance after adjustments. 3,4,30,42,43 Sinning et al 7 reported that a severe increase in sPAP measured preoperatively was associated with an increased risk of death (hazard ratio [HR],…”
Section: Discussionmentioning
confidence: 99%